The Reconstruction of protolanguage Tidore and Tobelo - Sulastri T. Gani; Vivit Zarqa Hi. Muhammad; Nurull Rizma Muhiddin; Agung Agung; Nur Fajrhi (Universitas Muhammadiyah Purwokerto, 2026)
This article aims to reconstruct the proto of two local languages spoken in North Maluku, Tidore (Td) and Tobelo (Tb) languages. North Maluku province is linguistically unique as it is home to two language groups, Austronesian and Non-Austronesian (Papuan). Despite its shared linguistic features, linguists argue that it is difficult to study language in this region because previous researchers have used different linguistic classifications. Languages in this area might be influenced by social, political, and economic conditions, and the strong contact between Austronesian and non-Austronesian languages significantly influences language use and development. Both Td and Tb are classified as members of Papuan language groups, particularly the North Halmahera stock. This study employs a descriptive qualitative method. The data are obtained through interviews with selected speakers using the 200 Swadesh words list. Several steps are performed in the data analysis stage. The first step is to describe the phonological system of each language, including phonemes, allophones, and their distribution. The step is followed by arranging the sound correspondence of the languages. The results of sound correspondence are used in the phonological reconstruction process to determine the proto-forms of the related languages. then continues with a diachronic comparative analysis to examine the historical relationship The result reveals that both languages have five vowels, /a/, /i/, /u/, /e/, /o/ and 19 consonants, /p/, /b/,/m/, /w/,/f/, /t/, /d/, /n/,/s/, /r/, /l/, /c// ɟ/, / ɲ/, /y/, /k/, /g/, /ŋ/, and /h/. The vowels of both languages appear to be stable. Each vowel segment in Td corresponds identically to its counterpart in Tb, suggesting these sounds were retained directly from the protolanguage without changes. Although the Td and Tb languages currently have 19 consonants, the reconstruction results only establish 16 proto-sounds, /*p/, /*b/, /*m/, /*w/, /*f/, /*t/, /*d/, /*n/, /*s/, /*l/, /*ɲ/, /*y/, /*k/, /*g/, /*ŋ/, and /*h/. This is because the phonemes /c/, / ɟ/, and /r/ in both languages do not show regular correspondence patterns.